On the Differentiability of Weak Solutions of an Abstract Evolution Equation with a Scalar Type Spectral Operator - Marat V. Markin (International Journal of Mathematics and Mathematical Sciences)
For the evolution equation 𝑦(𝑡)=𝐴𝑦(𝑡) with a scalar type spectral operator 𝐴 in a Banach space, conditions on 𝐴 are found that are necessary and sufficient for all weak solutions of the equation on [0,∞) to be strongly infinite differentiable on [0,∞) or [0,∞). Certain effects of smoothness improvement of the weak solutions are analyzed.